Myricetin inhibits the generation of superoxide anion by reduced form of xanthine oxidase. (15th April 2017) - Zhang, Cen; Zhang, Guowen; Liao, Yijing; Gong, Deming
Highlights: Myricetin inhibited O2 − generation due to the reduced form of XOD. Myricetin reversibly inhibited the formation of uric acid in a mixed-type manner. Myricetin bound to the site around isoalloxazine ring in the FAD domain. Van der Waals forces and hydrogen bonds dominated the binding process. Binding of myricetin to XOD induced the conformational change of XOD. Abstract: Myricetin, a plant-derived flavonol, was found to inhibit the formation of uric acid in a mixed-type manner with IC50 value of (8.66 ± 0.03) × 10 −6  mol L −1 and more potently inhibit the generation of superoxide anion (O2 − ) catalysed by xanthine oxidase (XOD) with IC50 value of (4.55 ± 0.02) × 10 −6  mol L −1 . Inhibiting O2 − generation by myricetin may be attributed to the reduced form of XOD with a substantially higher reduction potential for FADH/FADH2 couple. Moreover, molecular docking verified that myricetin bound to the site around isoalloxazine ring in the flavin adenine dinucleotide (FAD) domain to block the diffusion of O2 − out of the FAD site, resulting in the transfer of another electron from FADH2 to O2 − to form hydrogen peroxide. This study has provided new insight into the role of myricetin in inhibiting XOD catalysis, which may be beneficial to improve myricetin's potential application in functional foods.